Fe-doped SnO(2) nanomaterial: a low temperature hydrogen sulfide gas sensor - Vaishampayan, Mukta V.; Deshmukh, Rupah G.; Walke, Pravin; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2008)
The effect of Fe-doping on the surface chemistry and gas-sensing properties of nanocrystalline tin oxide is analyzed. The pristine and Fe-doped SnO(2) are synthesized by the modified Pechini citrate route that produces around 40 and 18 nm sized nanoparticles, respectively. 1 at.% Fe-doped SnO(2) shows significantly high selectivity towards hydrogen sulfide gas with capability to detect even 10 ppm of hydrogen sulfide at room temperature, with change of about one order of magnitude in the resistance within 5-15 s. In comparison, pristine SnO(2) shows negligible response towards H(2)S at room temperature. The ideal response and recovery of Fe-doped SnO(2) at low concentration of gas suggests Fe-doped SnO(2) nanomaterial as a potential low cost, low temperature H(2)S gas sensor. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Fe-doping; H(2)S; nanomaterial; Sensor; tin oxide